2015
DOI: 10.1109/jstars.2014.2378795
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Soil Moisture in Mountain Areas Using SVR Technique Applied to Multiscale Active Radar Images at C-Band

Abstract: This paper presents an approach for retrieval of soil moisture content (SMC) from different satellite sensors with a focus on mountain areas. The novelties of the paper are: the extension of an already developed method to coarse resolution data (150 m) in mountain environment with high land heterogeneity, with only VV polarization and the proper selection of input features. During the result analysis, several algorithm characteristics were clearly identified: 1) the performances showed to be strongly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 62 publications
3
31
0
Order By: Relevance
“…Many studies have highlighted the importance of exploiting additional vegetation information provided by optical remote sensing for retrieving soil moisture from a vegetated area [21][22][23][45][46][47]. The indices NDVI and LAI are among the most widely used vegetation indices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have highlighted the importance of exploiting additional vegetation information provided by optical remote sensing for retrieving soil moisture from a vegetated area [21][22][23][45][46][47]. The indices NDVI and LAI are among the most widely used vegetation indices.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the radar data used in this study was C-band data from the Sentinel-1 satellite and in the single polarization mode (VV polarization). Previous studies have shown that VV polarization is not the most relevant polarization in the soil moisture retrieval process [29,44,45]. Also, the studied areas are under vegetation cover and the C band is not considered the best band for exploiting in areas with vegetation cover.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Physically based models have been applied to retrieve the SM successfully [6,7], but these models require extensive information regarding the vegetation and soil surface, which might be difficult to obtain at a larger scale. Several empirical, regression or machine learning based models have been used to retrieve the SM with relative success (e.g., [8][9][10][11][12]). A major disadvantage of these models is the requirement of extensive in situ SM to calibrate the models.…”
Section: Introductionmentioning
confidence: 99%
“…leads to the same electromagnetic response at the sensor. In addition to this, one has to take into account the sensitivity of the microwave signal to various target properties (e.g., soil roughness and vegetation coverage) and the effect of topography and land use heterogeneity [12,115,116]. Soil moisture retrieval has been addressed by several methodologies that fall into the following main categories:…”
Section: Retrieval Of Essential Variables: Soil Moisturementioning
confidence: 99%